Tea (Camellia sinensis) Production, Opportunities, Challenges, and Future Prospects in Ethiopia - Nagassa Dechassa; Misgana Merga (Advances in Agriculture)
Tea is one of the most commonly consumed stimulants in the world. It is cultivated commercially at Wushwush, Gumero, and Chewaka tea estate plantations, in Ethiopia. Over 150,000 hectares of Ethiopian land are available for the production of high-quality tea, but only 3,099 hectares are currently under cultivation. In Ethiopia, tea clones Mlk-1, Mlk-2, 11/56, S-15/10, FNF, 11/4, 6/8, L6, B9, Chai, BB-35, and SR-18 are commercially grown. Ethiopia’s favorable environmental conditions for high-quality tea production increased the availability of tea throughout the year, and the availability of a sufficient labor force is a significant opportunity for tea companies. However, tea production is still infant because it needs huge capital to establish the tea plantations and production, the pest problems, limitations of improved technologies like cultivars, and lack of tea genetic resources. Besides, there is a limitation of comprehensive research to develop innovative technologies in the case of tea agronomic, breeding, and pest management for Ethiopian conditions. Thus, the government should invite investors and facilitate necessary things for the investors to increase the tea industry in the country. The tea research should be strengthened for the development and implementation of the appropriate technologies.